The Interpretation of Biogeochemical Growths on Gold Coins from the SS Central America Shipwreck: Applications for Biogeochemistry and Geoarchaeology - Erik B. Melchiorre (Journal of Marine Science and Engineering, 2019)
Black crusts that formed on gold coins recovered from the 1857 shipwreck of the SS Central America played a key role in their preservation in a near original state. Within a few years of the sinking, the significant quantities of iron and steel on the shipwreck produced laminar geochemical precipitates of fine-grained iron minerals on the coins. This coating served to armor the coins from future chemical or biological attacks. Once coated, the coins were colonized by at least two distinct populations of gold-tolerant bacteria that precipitated abundant nanoparticulate gold in the black crust material and produced biomineralized bacteria in a web-like mat. Above this middle layer of black crust, the outer layer consisted of a geochemical reaction front of euhedral crystals of iron sulfate and iron oxy-hydroxide species, formed by the interaction of seawater with the chemical wastes of the bacterial mat. Understanding this process has application for assessing the diverse and extreme conditions under which nano-particulate gold may form through biological processes, as well as understanding the conditions that contribute to the preservation or degradation of marine archaeological materials.